Are static posturography-assisted biofeedback exercises effective in Parkinson's disease? - Yakşi, Elif; Yaşar, Mustafa Fatih; Türel, Canan Akünal; Balcı, Muhammed (Arquivos de Neuro-Psiquiatria, 2022)
Background Parkinson disease (PD) is a progressive condition that causes disorders in movement and balance.Objective To evaluate the effectiveness of static posturography-assisted biofeedback exercises in PD-related balance disorder.Methods We screened 83 patients, 48 of whom were enrolled, and 41 completed the study. The sample was randomized into two groups, one submitted to static posturography-assisted biofeedback exercises and the other, to a conventional exercise program. The patients in the biofeedback group (n = 20) performed biofeedback exercises in addition to conventional balance exercises. Those in the conventional exercise group (n = 21) performed classic balance exercises. Both groups were treated for 20 minutes per session 3 times a week for 6 weeks. The patients were evaluated using the Hoehn and Yahr Scale, the Movement Disorder Society–Unified Parkinson's Disease Rating Scale (MDS-UPDRS), the Berg Balance Scale (BBS), the Tinetti Gait and Balance Assessment (TGBA), the Timed Up and Go Test (TUG), the Tandem Stance Test (TST), a Turkish version of the Stanford Health Assessment Questionnaire (HAQ), and the Beck Depression Inventory (BDI) before and at the end of the treatment.Results No statistically significant differences were observed between the two groups in terms of the MDS-UPDRS, BBS, TGBA, TST, TUG, HAQ, or BDI measurements before and after the treatment (p > 0.05).Conclusions Improved balance parameters were observed following balance training in the patients with PD, although static posturography-assisted biofeedback exercises appeared to provide no additional benefit. However, larger, randomized controlled trials are needed to investigate their effectiveness.
Keywords: Biofeedback, Psychology; Exercise; Parkinson Disease; Postural Balance